SENI RAKYAT DALAM DIMENSI INDUSTRIAL - - Sutiyono (FBS UNY, 2012)
This article discusses the role and position of folk art in facing industrialization era. When facing this, folk art, in terms of its presentation, is divided into two. First, folk art should surrender to the power of industrialization. It has to limit its time and space performance in which it has to be recorded in a smaller package. The social followers then only need to play the recording to be able to enjoy the performance. Second, the folk art is presented in a complete form without any reduction. The social followers, thus, prefer to its live performance in its original version. They play a role as a form of cultural resistance in facing this globalization and industrialization era.